WATER QUALITY ASSESSMENT ON THE COAST OF DESA MUSI, KECAMATAN GEROKGAK, BALI - Amelia, Jasmine Masyitha; Maharani, Made Dwipa Kusuma (Jurusan Perikanan dan Kelautan, 2024)
The northern coast of Bali possesses significant natural resource potential, particularly in Desa Musi, Kecamatan Gerokgak, which serves as a site for fish and seaweed cultivation managed by the local communities. However, some of these aquaculture activities lack adequate wastewater management systems. This study aimed to evaluate the water quality along the coast of Desa Musi, Kecamatan Gerokgak, Bali. A quantitative descriptive approach was employed, with purposive sampling conducted at selected locations along the coastal area. The water quality parameters assessed included salinity, pH, temperature, phosphate, ammonia, lead, and cadmium concentrations. The findings revealed that the coastal waters of Desa Musi generally support marine biota. However, the concentrations of lead and cadmium exceed the threshold values stipulated by Kep-51/MenKLH/2004. These results underscore the need for regular water quality management and monitoring to ensure environmental sustainability and support the livelihoods of the local community.Keywords: Coastal ecosystems, environmental monitoring, heavy metals.